Gender, Integration, and Labor Market Access: The Case of Syrian Refugees in Germany - Al-Mekhlafy, Feras (AUC Knowledge Fountain, 2026)
Germany hosts one of the largest populations of Syrian refugees in Europe, making their successful labor market integration critical for social and economic stability. This study investigates the gender gap among Syrian refugees in Germany within the broader refugee–native labor market gap. Using cross-sectional data from the 2022 SOEP refugee survey, it applies a Heckman two-step selection model to jointly analyze employment and wage outcomes while correcting for selection bias. Results reveal that structural barriers (e.g.: legal and bureaucratic) and compositional factors (e.g.: human capital) rather than wage discrimination drive most observed disparities. Female refugees face significantly lower employment probabilities, highlighting persistent access barriers, yet once employed, their wages do not differ systematically from men’s after accounting for selection. Human capital indicators such as vocational or college education and prior full-time work experience strongly predict employment, though their wage effects vanish after bias correction. Integration factors like German language proficiency, social interaction with locals, and completion of BAMF courses positively influence employment, while current course enrollment reduces wages due to time trade-offs. Regional differences favor West Germany, and unemployment history exhibits a “scarring effect,” lowering employment chances. Findings highlight underemployment and suggest that gender inequality lies primarily in labor market entry rather than pay. By leveraging recent data and robust methodology, this study contributes new evidence to refugee integration research and informs policies aimed at reducing structural barriers.